Comparative study of the effect of the Hubbard coefficient U on the properties of TiO2 and ZnO. (June 2021) - Fernández, A.C. Rossi; Schvval, A.B.; Jiménez, M.J.; Cabeza, G.F.; Morgade, C.I.N.
Graphical abstract: Highlights: In TiO2, as the U factor increases, both the BG and the unit cell parameters increase. For ZnO, as U increases, BG increases but the structure parameters decrease. The BG value reaches a maximum from which it decreases in the case of titania. An increasing and linear behavior is observed for the BG width on ZnO. The effects of Ud parameter are especially visible in CB for TiO2 and in VB for ZnO. Abstract: First-principles calculations combined with Hubbard U correction based on Density Functional Theory has been used to investigate the effect of its inclusion on electronic, structural, and optical properties and to reproduce correct band gap for TiO2 (anatase and rutile) and ZnO (wurtzite) structures. The effect of the implementation of U for only metal (Ti or Zn) d state (U d ) or for both 3 d (U d ) and O p (U p ) states was investigated to exploring changes in valence and conduction bands and their origin. Bader's charge analysis has been used to revealing the nature of chemical bonding. We can conclude that for both TiO2 polymorphs as the U d factor increases, both the BG and the lattice parameter increase. On the contrary, for ZnO, as U d increases the value of BG increases but the cell parameter decreases. The optimal values correspond to U d =8 eV (TiO2 ) and U d =13 eV (ZnO). The corresponding optical properties using U d, such as real and imaginary parts of dielectric function, reflectivity R(ω), refractive index n(ω), extinction coefficient k(ω), absorption coefficient α(ω) and electron energy loss function L(ω) has been calculated. It is important to highlight that the curves obtained considering the inclusion of the U d show an excellent agreement with those reported experimentally.